Development Of Social Science Learning Media Based On The Dance Song Tarian Penghancur Raya To Improve The Social Sensitivity Of Students Of GIKI 3 SMP SURABAYA: Pengembangan Media Pembelajaran IPS Berbasis Lagu Tarian Penghancur Raya Untuk Meningkatkan Kepekaan Sosial Siswa SMP GIKI 3 Surabaya - Rachmah Fitriyanti Hadju (Jurnal Dialektika Pendidikan IPS, 2026)
This study aims to determine the development process and effectiveness of social studies learning mediabased on the song “Tarian Penghancur Raya” in improving the social sensitivity of eighth-grade students at SMPGIKI 3 Surabaya. This research used the Research and Development (R&D) method with the ADDIE model, whichconsists of analysis, design, development, implementation, and evaluation stages. The research subjects were 33students of class VIII-A. Data collection techniques included questionnaires, observation, as well as pretest andposttest. The research instruments consisted of expert validation sheets (material and media experts), social sensitivityquestionnaires, and student response questionnaires. The results showed that the developed learning media wascategorized as highly feasible, with material expert validation reaching 90% and media experts stage 1 was 64.58%after being revised by media stage 2 to 85.42%. The learning media was also proven effective in improving students’social sensitivity, as indicated by the increase in the average pretest score from 66.33 to 93.56 in the posttest. The N-Gain score of 0.81 was categorized as high. Students’ responses to the learning media were classified as very good,with a percentage of 94.55%. Therefore, the social studies learning media based on the song “Tarian PenghancurRaya” is effective in improving students’ social sensitivity.